Proyecto de factibilidad para la creación de una empresa productora y comercializadora de pulpa de guayaba en el cantón el Pangui, provincia de Zamora Chinchipe para el año 2016 - Rojas Ponce, Gicella Anabel (2017)
The present research topic entitled "FEASIBILITY PROJECT FOR THE CREATION OF A PRODUCTION AND MARKETING COMPANY OF PULPA DE GUAYABA IN EL CANTÓN EL PANGUI, PROVINCE OF ZAMORA CHINCHIPE" was carried out with the purpose of knowing if it is viable or not to start the execution of the same, and with that to satisfy the needs of the current man, who for lack of time, can not prepare their food habitually, but q seeks the way that this work is easy and above all saving them time, and mainly are healthy and natural products, for this reason is born this investment project, to try to solve the problem found in the canton and therefore the non existence of a company dedicated to this activity.. Posing for its development as main objective: To determine the Feasibility for the creation of a company producing and selling guava pulp in the canton of Pangui, province of Zamora Chinchipe; and, as specific objectives: With the market study could determine product demand; whose unmet demand in the town were 74938 pounds of guava pulp, which still requires this product to meet your need. Evaluate the demand and supply of the company producing and marketing guava pulp in the canton El Pangui through the market study. Establish the technical feasibility of the proposal through the corresponding technical study. Design the organizational and legal structure, propose a manual of functions Elaborate the study of income and expenses of the project through the financial study. Evaluate financially and economically the proposal presented in this investment project. For this purpose, the analysis was based on methods such as inductive, deductive, statistical and descriptive, as well as the application of research techniques such as direct observation and the application of surveys. In the market study surveys were conducted in the canton el Pangui with a sample of 330 families and 37 local, with the analysis of these shows that there is an effective demand of 87.994 units of pound of guava pulp, on the market of 13,056 units of guava pulp with unsatisfied demand of 74,938 pounds of guava pulp, which determines that the project is viable. The product will be named "Guayaba pulp", its price is fixed based on production costs plus a profit margin, and distribution will be made in major markets, shopping malls, and stores. The installed capacity of the plant is 52,000 pounds of guava pulp per year, being a new company this will start operations with 70% of its capacity, which will increase year by year. Through advertising will achieve the positioning of the product and the company in the market of the canton the Pangui, advertising will be done through a medium. In the technical study was established the micro and macro location is attached a map and a sketch of the location of the company and location factors, the plant will be located in the canton the Pangui province of Zamora Chinchipe, Barrio Reina del Cisne Av. National Police and Cornelius Troy. The organizational study will ensure that the company has an adequate structure and organization in each of the areas, and with a timely definition of hierarchical levels, and that it has a well-defined function manual that guides each member to accuracy the position to play and the responsibilities that this carries. The required investments are expressed in fixed assets, deferred assets and current assets or working capital, fixed assets amount to $ 35,376.28, deferred assets of $ 1,974.00 and with working capital amounts to the amount of US $ 8,265.80 giving us an overall investment of US $ 45,976.08 for its financing will be used to external sources, such as BanEcuador.BP In the economic evaluation we have a Net Present Value is $ 35,800.37, the Internal Rate of Return is 25.36%, which is greater than the market opportunity rate, the Cost Benefit Ratio is 1.30 for each dollar invested the company has a profit of 0.30 cents, investment recovers in 2 years, 9 months 11 days, the project is not sensitive to a maximum cost increase by 13.43% and a decrease in the minimum income of 5.14%, higher than these percentages the project becomes sensitive. The conclusions and recommendations are established at the end of the project.